The Effect Of Instagram Content And Visualization @Jktgo On The Intention To Visit Among The Community - Hidayat, Andrian Rachmat; Edhy Aruman LSPR, Akhmad (Journal of Comprehensive Science, 2025)
Instagram has become a dominant social media platform that influences public decisions, particularly when selecting travel destinations and culinary spots. The @JKTGO account, with 1.4 million followers, leverages visually appealing content to shape the public's visit intentions. This study analyses the impact of Instagram exposure and content visualization on the intentions of the public to visit. This study uses SOR theory with a quantitative method using a survey of 385 respondents. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that both Instagram exposure and content visualization significantly influence visit intentions, with content visualization having a more substantial impact. The study concludes that visual elements are crucial in digital marketing strategies, particularly in enhancing the appeal of travel and culinary destinations. These findings can assist destination managers, and businesses develop more effective promotional strategies.